Intervensi Psikoedukasi dalam Meningkatkan Orientasi Masa Depan Remaja yang Berhadapan dengan Hukum di Lembaga Pembinaan Khusus Anak (LPKA) - Naomi Soetikno; Fiona Jankidevi; Zahwa Angelika; Erica Rahma Prisciella (Social Science Academic, 2026)
Adolescents who are confronted with the law are an age group that is in the phase of identity development, so they need guidance that includes psychological and disciplinary development. A person's ability to set goals, plan steps, and evaluate their future are important components that must be developed. The purpose of this study is to find out how effective psychoeducational interventions are in improving the future orientation of fostered children in the Special Children's Development Institute (LPKA). This study uses a quantitative approach with a one-group pretest-posttest design on 27 LPKA fostered children. The measurement was carried out using the Future Orientation Questionnaire (FOQ) which measures three main dimensions, namely motivation, planning, and evaluation. Interventions are carried out through a series of psychoeducational activities which include self-reflection worksheets, drawing mandalas, focused group discussions, future planning worksheets, motivational seminars, and the preparation of dream maps. Data were analyzed using descriptive statistics, normality test, and Wilcoxon Signed Rank Test. The average future orientation score increased from 80.59 in the pretest to 85.89 in the posttest with a gain score of 5.30. The results of the Wilcoxon test showed that there was a significant difference between pretest and posttest scores (Z = -2.864; p = 0.004) there was a decrease in the number of participants who experienced scores below the low category. A total of 20 participants experienced an increase in scores after participating in the intervention. Psychoeducational interventions have proven to be effective in improving the future orientation of LPKA fostered children. Programs that combine self-reflection, emotion recognition, and the development of life goals can help participants build a clearer and more flexible future orientation as a provision during the process of social reintegration